Case Report: Detection of Transferrin in a Dog Suspected of Having Cerebrospinal Fluid Rhinorrhea - Kinoshita, Kosuke; Nishida, Hidetaka; Kanegi, Ryoji; Nakamoto, Yuya; Tanaka, Toshiyuki; Shimamura, Shunsuke; Kusumoto, Kazuhito; Akiyoshi, Hideo (Frontiers in Veterinary Science, 2022)
A 12-year-old Yorkshire terrier was referred for epileptic seizures and nasal discharge. The fluid was clear and serous. Cerebrospinal fluid (CSF) rhinorrhea was suspected, based on clinical signs and MRI findings. In humans, analysis of nasal secretions to determine the concentration of glucose and brain-type transferrin has been widely used clinically in order to confirm the presence of CSF rhinorrhea. The glucose concentration in the nasal discharge was 74 mg/dL. Serum-type and brain-type isoforms of transferrin were detectable in the nasal sample. The concentration of glucose and brain-type transferrin could be useful for diagnosing CSF rhinorrhea.